Effect of video and pamphlet-based educational program on the quality of life of patients with chronic obstructive pulmonary disease: A quasi-experimental study - Jani, Mohammad Reza; Salehi, Hoda; Sarvari, Mohammad Hadi; Mohsenizadeh, Seyed Mostafa (Journal of Nursing Reports in Clinical Practice, 2023)
The present study aims to determine the effect of two educational methods of pamphlets and videos on the quality of life (QoL) of patients with chronic obstructive pulmonary disease (COPD). This study is quasi-experimental. Patients with COPD who are admitted to and treated at the internal department of Shohada Qaen Hospital make up the population of this study. Giving an informative pamphlet was used as the training intervention's first group while showing an instructional video (CD) was used as its second group. The patients were given educational pamphlets or educational CDs throughout their hospital stay, and they were instructed to implement the educational materials at home. With the use of the SF-36 tool, the QoL of both groups of patients was assessed at the time of discharge and served as a baseline for comparison one month later. A total of 80 COPD patients participated in this study. Among 80 participants, 40 of them were in the educational pamphlet group and 40 of them were in the educational videos group. According to the SF-36 questionnaire, the mean score of QoL before and after the intervention in the educational videos group was 37.84 (SD=11.35) and 59.97 (SD=11.31), respectively, which indicated a significant difference after the intervention (P≤0.001). The mean score of QoL before and after the intervention in the educational pamphlet group was 31.93 (SD=13.50) and 45.63 (SD=14.27), respectively, which indicated a significant difference after the intervention (P<0.001). Overall, based on the obtained results, self-care education through video content and pamphlet improves the level of QoL in patients with COPD. Therefore, medical staff, especially nurses, can improve QoL in patients with COPD by using video and pamphlet self-care educational methods.